2013
DOI: 10.3762/bjnano.4.106
|View full text |Cite
|
Sign up to set email alerts
|

Structural development and energy dissipation in simulated silicon apices

Abstract: In this paper we examine the stability of silicon tip apices by using density functional theory (DFT) calculations. We find that some tip structures -modelled as small, simple clusters -show variations in stability during manipulation dependent on their orientation with respect to the sample surface. Moreover, we observe that unstable structures can be revealed by a characteristic hysteretic behaviour present in the F(z) curves that were calculated with DFT, which corresponds to a tip-induced dissipation of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This triggers a reversible (as was shown by as was shown by our calculations of the force-distance curve for retraction of the tip) reconfiguration of the Si dimer at the tip apex. We have previously shown that this sudden distortion of the tip is associated with energy dissipation and hence may manifest itself in the dissipation signal, providing an additional distinct feature for the dimer tip 30 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This triggers a reversible (as was shown by as was shown by our calculations of the force-distance curve for retraction of the tip) reconfiguration of the Si dimer at the tip apex. We have previously shown that this sudden distortion of the tip is associated with energy dissipation and hence may manifest itself in the dissipation signal, providing an additional distinct feature for the dimer tip 30 .…”
Section: Resultsmentioning
confidence: 94%
“…To overcome these difficulties, several tip identification protocols have been proposed, such as determining the tip apex chemical identity by performing spectroscopy measurements on ionic KBr 25 , imaging of the Cu:O surface 26 , TiO 2 27 , MgO 28 , Si(100) 29 30 and the hydrogen-passivated Si(111) surface 24 . Fuiju and Fijihira 31 proposed a new sample holder where two surfaces can be mounted side by side: the CaF 2 (111) surface to be used for tip characterisation, while the other contained a mixed assembly of thiolates on the Au(111) surface.…”
mentioning
confidence: 99%
“…This approach has been an interesting approach to simulate AFM images, , but this does not fully capture the nature of the tip/sample forces. For this reason, many other works have modeled the complex interaction processes between explicit probe tips and surfaces by first-principles calculations. , Accordingly, it is important to take account that the chemical complexity of the probe tips is the biggest challenge for its modeling in the NC-AFM simulations, even for the standard silicon usually used in the experiments. On the other hand, according to Si probe tip models proposed in Caciuc et al, , Oyabu et al, Kantorovich et al, and Bamidele et al, just the terminal probe tips indeed dominate the short-range forces for each surface atomic site.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, the use of qPlus DFM, with its associated ability to exploit probe oscillation amplitudes as small as 20 pm, will produce much-enhanced sensitivity to short range forces and will facilitate direct comparison of experimental force-distance curves and force-fields (see discussion below on atomtracking-enabled 'grid spectroscopy') with the results of our DFT simulations of the tip-sample interaction. In addition to carrying out a detailed characterisation of Group III-and Group V-terminated tip apices (for a variety of structures, as for our previous work on Si-terminated tips [35]), we will also investigate the interaction of (non-Group-III-)metal-terminated tips (Au-, Mn-, and W-) with III-V surfaces. A particular goal throughout will be the identification of specific spectral signatures in the force-distance curves (and associated dissipation-distance curves) which will enable us to classify the experimental tip apices into various classes (e.g.…”
Section: Iiia Chemical Contrast On Iii-v Surfacesmentioning
confidence: 99%